Multi‐site aerodynamic optimization of wind turbine blades for maximum annual energy production in East Iran. Issue 6 (22nd February 2020) - Azizi, Mahdi; Jahangirian, Alireza
Abstract: Aerodynamic optimization of a horizontal axis wind turbine blade is performed for maximizing total annual energy production in three different sites located in the east part of Iran. While most researches have focused on the optimization of wind turbine blades for a specific location or air velocity, the main objective in practical problems is to find the best single design for multiple locations giving the highest energy output. The current paper addresses this issue and shows that multi‐site optimization of wind turbine blades is the key to maximizing energy extraction at multiple sites while reducing the manufacturing costs by proposing one optimum blade for all sites. In order to achieve this goal, the known Riso wind turbine blade is used as the base geometry and is optimized using a modified blade element momentum (BEM) theory and genetic algorithm. The objective function is maximizing sum of energy production at the selected sites. Blade twist and chord length distributions are chosen as design parameters. By running various optimization cases, it is shown that the multi‐site optimum blade has the highest sum of annual energy production by 4.45% increase compared with the Riso wind turbine blade. Abstract : Aerodynamic optimization of a horizontal axis wind turbine blade is performed for maximizing total annual energy production in three different sites located at the east part of Iran. The current paper shows that multi‐site optimization of wind turbine blades is the key for maximizing energy extraction at multiple sites while reducing the manufacturing costs by proposing one optimum blade for all sites.